The Influence of Maladaptive Daydreaming on Celebrity Worship Among Muslim Early Adult K-Pop Fans in Indonesia - Azizah, Fina Fathimatun; Kusumaningrum, Fitri Ayu (Unisia, 2025)
Celebrity worship has become increasingly prevalent in the digital age, particularly among young adults engaged in global fan cultures such as K-pop. This study explores how maladaptive daydreaming influences the intensity and nature of celebrity worship among Muslim early adults in Indonesia. The research aims to understand whether immersive and emotionally driven fantasy behaviors contribute to varying levels of celebrity attachment. Using a quantitative correlational design, data were collected from 253 participants aged 19 to 35 who identified as active K-pop fans and adherents of Islam. Participants completed two standardized instruments: the Maladaptive Daydreaming Scale and the Celebrity Attitude Scale, which measures three dimensions of celebrity worship—entertainment-social, intense-personal, and borderline-pathological. Statistical analyses included Pearson’s correlation and multiple linear regression. Findings revealed that maladaptive daydreaming significantly predicts both intense-personal and borderline-pathological celebrity worship, but not the entertainment-social dimension. These results suggest that fantasy-based coping mechanisms are more closely associated with emotionally immersive and obsessive fan behaviors than with social enjoyment of celebrity culture. The data support theoretical models that link maladaptive fantasy to parasocial attachment, highlighting the psychological complexity of media engagement. This study contributes to the growing body of literature on parasocial phenomena by integrating cultural and religious context, demonstrating how internal cognitive processes intersect with modern fan practices. The results underscore the importance of early identification and intervention strategies to mitigate emotional dependency and psychological distress among media consumers, especially in highly immersive digital environments.